TRADEMARK LEGAL PROTECTION IN THE HALAL CERTIFICATION PROGRAM FOR MSMES - Harmono; Yosi Andri, Gusti; Solichin; Annisa Rahmadina, Adji; Fara Winda (Cirebon International Conference on Education and Economics Proceeding, 2024)
The halal certification program has become important for Micro, Small, and Medium Enterprises (MSMEs) who want to market their halal products widely. However, in the context of trademark legal protection, MSMEs often face challenges in ensuring that their trademarks are properly protected in halal certification programs. This study aims to analyze the mechanism of trademark legal protection for MSMEs involved in halal certification programs. The research method used is literature study and policy analysis related to trademark legal protection and the implementation of halal certification programs for MSMEs. The results of the study show that cooperation between halal certification bodies and trademark protection agencies is very important to ensure that the trademark rights of MSMEs are effectively protected. The conclusion of this study is the importance of a better understanding of trademark legal protection for MSMEs involved in halal certification programs. Recommendations for relevant parties include increased cooperation between halal certification bodies and trademark protection agencies, as well as increased legal awareness for MSMEs on the importance of protecting their trademarks in the context of halal certification programs.